MULTIMEDIA APPLICATIONS TOURISM OBJECT FRAMES USING VISUAL BASIC 6.0 - Samlawi Samlawi; Yudi Irawan Chandra, SKom, MMSI (Jurnal Sistem Informasi, 2005)
Discussing about the world of tourism, particularly tourism dikepulauan thousand who have been prepared using Visual Basic 6.0 and is expected to ease in obtaining information about natural conditions, the panorama follows the excess-the excess of each, which in turn can help nature lovers, especially for tourists or research .